Supporting children’s emotional development : guide for parents and early childhood teachers - Swathy Saradha 1987- (2022)
When children begin attending early childhood education from an early age, they may face various challenging behaviours like hitting, biting, social withdrawal, seeking attention and other emotional challenges. This paper discusses how teachers and parents can encourage and support children to overcome these obstacles over time through positive communication, environment, and atmosphere, and assist them in developing their emotional behaviour. The targeted audience for this paper would be the early childhood teachers and parents who are the pillars of strength in supporting the children’s emotional development. The research is mainly done by examining academic sources and reflecting on my personal experience of being a teacher in a preschool for over 4 years in Iceland.